Critical role of HLA-DR?* binding peptides' peripheral flanking residues in fully-protective malaria vaccine development (2017)
A vaccine candidate component must fit perfectly into the antigen presenting HLA-DR?* molecule's groove (or canonical nonapeptide) peptide binding region (PBR) during antigen presentation to the T-cell receptor (TCR), conforming a specific and stable macromolecular complex and induce an appropriate immune response. Antigen's peripheral flanking residues (PFR, positions (p) -p2 and p10) must thus establish strong interactions with the HLA-DR?* - TCR complex. These amino acids (aa) have specific physico-chemical characteristics enabling differentiation between non-protective but antibody-inducer (NPAI), short-lived protection inducer (SLPI) and long-lasting protection inducer (LLPI) peptides when used as an antimalarial vaccine component. Their identification (through 1H-NMR and Aotus monkey immunization) and proper modification contributes to a logical and rational methodology for long-lasting and protective immunological memory. © 2017 Elsevier Inc.